Effect of Hypnosis in Adolescents: A Narrative Review - Farzaneh Rashidi Fakari; Zahra Atarodi Kashani; Shiva Alizadeh; Afsaneh Talebi; Reza Pakzad; Fatemeh Abdi (Mazandaran University of Medical Sciences, 2023)
Background: More than half of reproductive-age women experience dysmenorrhea, which can reduce their quality of life. The treatment options for dysmenorrhea are medications and alternative therapies. The tendency to use alternative therapies, such as hypnotherapy has increased.  Objectives: This study aimed to carry out a narrative review to evaluate the effect of hypnosis on dysmenorrhea in adolescents.  Methods: EMBASE, Web of Science, Scopus, Google Scholar, PubMed, Cochrane library ProQuest and clinicaltrials.gov were searched up to 2021 using the following keywords "dysmenorrhea", "hypnosis". The quality of studies was assessed by Cochrane collaboration's tool and the risk of bias in the non-randomized studies of interventions (ROBINS-I) tool. Results: Nine studies with a sample size of 5203 participants were included. The hypnosis intervention similar to drug therapy was effective in reducing the intensity of dysmenorrhea and improving the women's quality of life. Dysmenorrhea pain scores in hypnosis and drug therapy groups were significantly lower than those at baseline, but pain scores in the drug therapy group were significantly lower than in the hypnosis group. Conclusions: Hypnosis can provide lasting pain relief compared to NSAIDs. Therefore, it is recommended that hypnosis as a complementary or alternative therapy reduce the intensity of dysmenorrhea in adolescents.